miR-30d Inhibition Protects IPEC-J2 Cells Against Clostridium perfringens Beta2 Toxin-Induced Inflammatory Injury - Xie, Kaihui; Yang, Qiaoli; Yan, Zunqiang; Gao, Xiaoli; Huang, Xiaoyu; Wang, Pengfei; Zhang, Juanli; Yang, Jiaojiao; Li, Jie; Gun, Shuangbao (Frontiers in Veterinary Science, 2022)
Clostridium perfringens beta2 (CPB2) toxin, one of the virulence factors of Clostridium perfringens (C. perfringens), can cause necrotizing enterocolitis in piglets. Accumulating evidences indicate that microRNAs (miRNAs) refer to the regulation of inflammatory processes. Previously, we discovered that miR-30d was differentially expressed between the ileum of normal piglets and C. perfringens type C-infected diarrheal piglets. Here, we found that miR-30d expression was lowered in CPB2 toxin-treated intestinal porcine epithelial cells (IPEC-J2) at different time points. Subsequently, we determined that miR-30d inhibitor attenuated CPB2 toxin revulsive inflammatory damage in IPEC-J2 cells and promoted cell proliferation and cell cycle progression, whereas miR-30d mimic had opposite results. In addition, we confirmed that Proteasome activator subunit 3 (PSME3) was a downstream target gene of miR-30d via a dual luciferase reporter assay, qPCR, and western blot. We also found that overexpression of PSME3 suppressed CPB2 toxin-induced inflammatory damage and promoted cell proliferation and cycle progression. Our results demonstrate that miR-30d aggravates CPB2 toxin revulsive IPEC-J2 cells inflammatory injury via targeting PSME3, thereby providing a novel perspective for the prevention and treatment of piglet diarrhea at the molecular level.